Индивидуально-психологические особенности специалистов сферы искусства с высоким уровнем продуктивности творческого воображения - Karpova, Viktoriia V.; Dikaia, Liudmila А. (Rossijskij psihologičeskij žurnal., 2016)
The paper discusses the problem of relations between creative imagination and psychological characteristics of specialists in the sphere of art. The paper also describes the methodology and procedure of the empirical study of the individual psychological characteristics of specialists in the sphere of art with a high level ofproductivity ofcreative imagination. The study involved 240 respondents: specialists in the sphere of art (artists, actors) and specialists not working in the eld of art. Theprocedure of research included the determination of the level of the productivity of creative imagination and psychological testing.When determining the level of the productivity of creative imagination, the authors applied the expert evaluation of art works; the respondents made these art works inthe monotypy technique. As a result, all the participants of the study were divided into subgroups of high and low productivity within their professional groups. Forpsychological testing the authors used the personality inventory FPI, questionnairefor evaluating volitional self-control (A. G. Zverkov and E. V. Eydman), “Choose aside” test (E. Torrance), “Incomplete gures” subtest (E. Torrance), and method of paired comparisons (V. V. Skvortsov). For statistical evaluation the authors carried out acomparative analysis using Student’s t-test. Statistica 13.0 software was used.The analysis of the obtained data demonstrated the individual psychological characteristics of the specialists of the sphere of art – artists and actors – with ahigh level of the productivity of creative imagination. The representatives of the sphere ofart with a high level of the productivity of creative imagination had ahigh levelofneurosis, irritability, and emotional lability. High scores on scales of shyness, depression, introversion, low level of volitional self-regulation were distinctive characteristics of artists with a high level of the productivity of creative imagination.Right-brained and mixed types of thinking dominated in them; the level of nonverbal creativity was high; elaboration had the highest score; self-actualization and respect were the main needs. Actors with a high level of the productivity of creative imagination had a reliably higher score on the scale of balance; the mixed type ofthinking was the dominant type; the level of non-verbal creativity was average;the need for self-realization had the highest score. В статье рассматривается вопрос о связи творческого воображения с психологическими характеристиками специалистов сферы искусства. В статье описаны методика и процедура проведения эмпирического исследования индивидуально-психологических особенностей специалистов сферы искусства с высоким уровнем продуктивности творческого воображения. В исследовании приняли участие 240 человек: специалисты сферы искусства (художники, актеры), специалисты, не работающие в сфере искусства. Процедура исследования включала определение уровня продуктивности творческого воображения и психологическое тестирование. При определении уровня продуктивности творческого воображения применялась экспертная оценка художественных произведений, выполненных испытуемыми в технике монотипии. В результате все участники исследования были разделены на высоко- и низкопродуктивных в рамках своей профессиональной группы. Для психологического тестирования использованы: личностный опросник FPI, опросник волевого самоконтроля А. Г. Зверькова и Е. В. Эйдмана, тест Е. Торренса «Выбор стороны», субтест Е. Торренса «Неоконченные фигуры», метод парных сравнений В. В. Скворцова. Статистическая обработка проводилась методом сравнительного анализа данных с помощью параметрического t-критерия Стьюдента. Использован пакет компьютерных программ Statistica 13.0. На основе анализа полученных данных выявлены индивидуально-психологические особенности, характерные для специалистов сферы искусства – художников и актеров – с высоким уровнем продуктивности творческого воображения. Представители сферы искусства с высоким уровнем продуктивности творческого воображения, независимо от специальности, характеризуются высоким уровнем невротичности, раздражительности, эмоциональной лабильности. Художников с высоким уровнем продуктивности творческого воображения отличают выраженная застенчивость, депрессия и интровертированность, низкий уровень волевой саморегуляции. У них доминируют правополушарный и совмещенный типы мышления; уровень невербальной креативности – высокий, особенно выражен показатель «разработанности»; основные потребности – в самореализации и в уважении. У актеров с высоким уровнем продуктивности творческого воображения достоверно выше показатель уравновешенности; доминирующий тип мышления – смешанный; уровень невербальной креативности – средний; наиболее выражена потребность в самореализации.